2009
DOI: 10.14430/arctic9
|View full text |Cite
|
Sign up to set email alerts
|

Bone Weathering in a Periglacial Environment: The Tayara Site (KbFk-7), Qikirtaq Island, Nunavik (Canada)

Abstract: ABSTRACT. Bone weathering analysis of the Palaeoeskimo Tayara site (Qikirtaq Island, Nunavik, Canada) documents site taphonomy in the Arctic periglacial environment. Like a majority of sites in the eastern Canadian Arctic, Tayara has a faunal assemblage dominated by marine mammals (seal, walrus, and beluga whale) and some terrestrial mammals (caribou, fox, and bear). Statistical and spatial analyses of five weathering stages reveal that large mammal bone preservation is generally good and does not seem to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Macroscopic cracking damage to the bone segments was rare, with only a single incident observed in the freeze‐dried treatment group. This observation was consistent with previous case studies that found that freeze‐thawing cycles could produce macroscopic longitudinal cracks on bone . However, this was an isolated observation, suggesting that macroscopic damage would be a rare effect of cold exposure (2% of long bone segments).…”
Section: Discussionsupporting
confidence: 92%
“…Macroscopic cracking damage to the bone segments was rare, with only a single incident observed in the freeze‐dried treatment group. This observation was consistent with previous case studies that found that freeze‐thawing cycles could produce macroscopic longitudinal cracks on bone . However, this was an isolated observation, suggesting that macroscopic damage would be a rare effect of cold exposure (2% of long bone segments).…”
Section: Discussionsupporting
confidence: 92%
“…The higher frequency of weathering on bones in the fill layer suggests fill material was exposed for longer periods than floor material. Despite the fact that there is very little actualistic or taphonomic research about the effects of root etching on faunal material (Denys, ; Lyman, ), it is most often seen on bones from shallow buried assemblages, where they are in the active root zone (Betts, ; O'Connor, ; Todisco & Monchot, ).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of root etching on bones from the fill layers may indicate that burial for most of the assemblage was sufficiently rapid to remove them from the active root zone (Todisco & Monchot, ). Based on the evidence that some of the bones were weathered (<6.5%), it is likely that the fill material was exposed to the elements for a longer time than the floor material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the medullary face, this process engendered the almost complete disappearance of the spongy bone, the digging of cupules caused by a localized chemical attack and the opening of fine longitudinal cracks typical of bone exposed to the action of meteorological and weathering agents (Behrensmeyer, 1978;Lyman and Fox, 1989;Lyman, 1992;Tappen, 1994). Such modifications are common in periglacial environments (Todd and Frison, 1986;Todisco and Monchot, 2008).…”
Section: Taxonomic and Taphonomic Identificationmentioning
confidence: 99%